(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article discusses innovative approaches to the development of thermally stable jelly filling based on low-esterified citrus pectin with the use of a complex food additive (CFA). The problem is driven by increasing demands for quality, safety, and nutritional value of flour-based confectionery products with jelly fillings. The main objectives are to enhance the thermal stability of the filling, stabilize its gel structure during baking and storage, and improve the organoleptic, physicochemical, and functional properties of the product. The study used model pectin systems with the addition of 0.1–0.2 % CFA and experimental samples of thermally stable jelly fillings. Evaluations included organoleptic characteristics, physicochemical properties, water-holding capacity, thermal stability, storage changes, as well as biological and energy value of the product. It was found that adding 0.15 % CFA promotes the formation of a stable three-dimensional gel structure, increases gel strength and thixotropy, enhances water-binding capacity, and reduces moisture loss during thermal processing and storage. The experimental samples exhibited improved organoleptic properties: transparent, homogeneous structure, stable color, and pleasant aroma. The optimal pectin content is 5 %, and the CFA concentration is 0.15 % of the total recipe mass. The formulation and technological scheme for producing thermally stable jelly filling were developed, and its biological, nutritional, and energy value were determined. The economic feasibility of implementing this filling in industrial production was demonstrated, ensuring increased stability, quality, and competitiveness of confectionery products.